Implementation of Islamic Business Ethics in TABAH Products at BMT NU Gambiran Banyuwangi - Asryva, Nabila Fikri; Ekaningsih, Lely Ana Ferawati (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research aims to analyze the mechanism of Islamic business ethics in TABAH Savings products at BMT NU Gambiran Branch, Banyuwangi, East Java. The research used a descriptive qualitative approach with informants selected using purposive sampling. Data was obtained through interviews, observation and documentation, including primary and secondary data sources. The research results show that the Islamic business ethics mechanism in TABAH Savings is based on a profit sharing agreement (Mudharabah), not interest. Profits are shared fairly between BMT and customers according to the agreement. The financial transaction process is carried out honestly and transparently. However, there are obstacles in the form of customers' inconsistency in saving due to weak intentions and unstable economic conditions. Apart from that, there are issues related to customers' lack of understanding of the sharia principles that are applied, which requires further education from BMT. As a solution, BMT NU provides a daily savings pick-up and drop-off service with no minimum nominal limit. The benefit of TABAH Savings for BMT NU is to increase the outstanding value of non-SIAGA savings, while for members, this product simplifies, secures and disciplines saving activities. In conclusion, the TABAH Savings mechanism at BMT NU Gambiran Branch is in accordance with the principles and provisions of Islamic business ethics , both in terms of the contract and its implementation. However, the issues that arise need to be handled through a more intensive approach towards customers.